Financial Performance Analysis of PT Fast Food Indonesia Listed on the Indonesia Stock Exchange in 2022-2023 - Elvina Diah Palupi; Ferida Ferida; Erwin Budianto (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the financial performance of PT Fast Food Indonesia Tbk (KFC franchise holder in Indonesia) in the period 2022–2023 using financial ratio analysis, including liquidity, solvency, activity, and profitability. Data are taken from the company's financial statements published on the Indonesia Stock Exchange (IDX). The results of the study show that the company experienced a significant decline in performance: (1) Liquidity ratios (Current Ratio and Quick Ratio) are below industry standards, indicating an inability to meet short-term obligations; (2) Solvency ratios (DER and DAR) show a high dependence on debt with DER reaching 440.24% (2023), indicating serious financial risk; (3) Activity ratios (TATO and ITO) are inefficient, reflecting suboptimal utilization of assets and inventory; (4) Profitability ratios (NPM and ROA) are negative, with ROA -10.69% (2023), indicating operational losses. The implications of this study emphasize the need for improved working capital management, debt restructuring, operational efficiency, and revenue-increasing strategies. Limitations of the study include the short analysis period and focus on one company. Suggestions for further research include the use of longer-term data and more comprehensive analysis.